2020
DOI: 10.15381/rpb.v27i1.17577
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la inoculación de plantas de Tarwi con cepas de Bradyrhizobium spp. aisladas de un lupino silvestre, en condiciones de invernadero

Abstract: El "tarwi" o "chocho" (Lupinus mutabilis Sweet) es la única especie cultivada del género Lupinus en América, valorado por su alto contenido proteico y capacidad de fijar nitrógeno en asociación simbiótica con rizobios. Su variabilidad genética está reforzada por aproximadamente 84 especies silvestres en el Perú. La presente investigación se realizó para evidenciar si los rizobios de una especie silvestre de lupino (Lupinus sp.) fueran capaces de nodular y promover el crecimiento del tarwi. Los nódulos radicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The bioinoculated treatment (C.Br+Ba) with a value of 4.43 significantly surpass both treatment Chem.trt and Control, with values 4.15 and 3.94 respectively. There are few publications on the effect of symbiotic bacteria such as Bradyrhizobium, which actively participates in biological nitrogen fixation (BNF) in legumes (Taco-Taype & Zúñiga-Dávila, 2020). In this context, in a recent study conducted by Monroy-Guerrero et al (2022), pointed out that the inoculated plants showed the best quantitative characteristics in the lateral inflorescence, as well as for the number of pods, weight of the pods and the number of locules increase to 165.1 %, 116.9 % and 14 % in comparison with the control treatment.…”
Section: Grain Production and Yield Componentsmentioning
confidence: 99%
“…The bioinoculated treatment (C.Br+Ba) with a value of 4.43 significantly surpass both treatment Chem.trt and Control, with values 4.15 and 3.94 respectively. There are few publications on the effect of symbiotic bacteria such as Bradyrhizobium, which actively participates in biological nitrogen fixation (BNF) in legumes (Taco-Taype & Zúñiga-Dávila, 2020). In this context, in a recent study conducted by Monroy-Guerrero et al (2022), pointed out that the inoculated plants showed the best quantitative characteristics in the lateral inflorescence, as well as for the number of pods, weight of the pods and the number of locules increase to 165.1 %, 116.9 % and 14 % in comparison with the control treatment.…”
Section: Grain Production and Yield Componentsmentioning
confidence: 99%
“…For this, it is important the use of an infective (capacity to nodulate) and effective (efficient for N2 fixation) Rhizobium in the legume, which implies the need to identify and inoculate strains of different origin (Fernández-Pascual et al, 2007). The inoculation of lupine roots with different strains of Rhizobium improves the levels and availability of nitrogen and carbon in the soils and therefore the vegetative development of the plant (Taco & Zuñiga, 2017). The objective of this research was to evaluate the effect of the inoculation of two Rhizobium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Tarwi (Lupinus mutabilis Sweet) is a legume cultivated in South American Andes, distributed from 2500 to 4500 m above sea level 1 . Its domestication occurred between 1800 and 3450 BP, and a cultivated area of 10,000 ha was estimated in Peru ca.…”
Section: Introductionmentioning
confidence: 99%